Controlling the risk of covid-19 transmission among hospital healthcare workers in Bima - Ilmidin, Ilmidin; Sarasnita, Nina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
COVID-19 has deeply disturbed the world with the confirmation of 318.6 million positive cases worldwide. There have been 14.1 thousand deaths and 4.2 million confirmed positives in Indonesia; the most common cluster of death cases is healthcare workers (HCw), totaling 2066 cases. This type of research is qualitative research with an exploratory descriptive design. The number of participants in this study is 12 people. The findings of this study revealed that there was excessive transmission in HCw, and one of the hospitals was temporarily closed because more than 20 HCw tested positive for COVID-19. In the psychology sub-category, there is still a level of stress felt by HCW dealing with COVID-19, and there is still a lack of special attention given to the anxiety and stress levels of these patients by hospitals. In the preventive care sub-category, the problem is that some hospitals still do not have OSH experts, so the risk assessment process and occupational health services are not carried out. As for the sub-category of medical device availability, further studies are still needed regarding the health system, especially in the availability of health devices in dealing with pandemics and other health-related disasters. Abstrak: Covid-19 sudah sangat meresahkan dunia dengan konfirmasi kasus 318,6 juta orang positif diseruh dunia. Di Indonesia terdapat 14,1 ribu meninggal dan 4,2 juta terkonfirmasi positif, kasus meninggal yang mendominasi adalah klaster tenaga kesehatan dengan jumlah 2066. Jenis penelitian ini adalah penelitian kualitatif dengan rancangan deskriptif eksploratif, jumlah narasumber dalam penelitian ini adalah 12 orang. Hasil penelitian ini menemukan adanya penularan berlebihan pada tenaga kesehatan, bahkan ada salah satu rumah sakit yang tutup sementara karena lebih dari 20 tenaga kesehatan terkonfirmasi positif covid-19. Pada sub kategori psikologi masih terdapat tingkat stress yang dirasakan oleh tenaga kesehatan yang menangani covid-19 dan masih kurangnya perhatian khusus pada kecemasan dan tingkat stress tenaga kesehatan oleh rumah sakit. Pada sub kategori preventif, masalahnya ada pada beberapa rumah sakit yang masih belum memiliki tenaga ahli K3, sehingga proses penilaian risiko dan serveilans kesehatan kerja tidak dijalankan. Sedangkan untuk sub kategori ketersediaan peralatan medis masih perlu kajian lebih lanjut dalam hal sistem kesehatan, terutama dalam ketersediaan perlatan kesehatan dalam menangani pandemi dan bencana lain terkait kesehatan.